Soldagem pontual por fricção (FSpW) de poliamida 6 - Gonçalves, Joel (Universidade Federal de São Carlos, 2015)
Friction Spot Welding (FSpW) is an innovative technique developed and patented in 2005 by the Helmholtz Zentrum Geesthacht (HZG) research center in Germany. FSpW uses the friction between a rotating tool and the workpieces to generate heat enough to cause diffusion across the interface to consolidate the weld. This new welding technology has been tested and optimized with the objective of produce overlap weld joints between two polyamide 6 plates. Full factorial design of experiments (24) and analysis of variance (ANOVA) allowed to explain the effects of weld parameters as rotational speed (RS), welding time (WT), plunge depth (PP), holding pressure time (HPT) and the interactions between these main parameters on the microstructural characteristics and mechanical strength of the joints. The rotational speed (RS) and welding time (WT), within the limits studied, had greater influence on the mechanical single lap shear strength of the joints that achieved up to 26 MPa. This behavior was related to the higher heat generation during the weld, reaching temperatures of up to 275°C, thereby increasing the welded area. The parameter holding pressure time (HPT), designed in this study allowed the cooling and solidification of the polymer under pressure, improving the weld surface finishing and avoiding defects as voids in the weld area. The most common failure for the joints with higher mechanical strength was the fracture of one of the plates while the joints with lower mechanical strength showed interface shear failure. The degree of crystallinity of PA6 in the welded area did not show a significant difference as compared to the base material. The molecular weight of PA6 in the welded area was reduced in the worst case 7% as compared to the base material (Mv = 41.800 g/mol), and that reduction occurred linearly with the increase of the temperature during the welding; however, that low degree of degradation was not found to affect the mechanical strength of the joints. These characteristics emphasize the potential of this FSpW as an alternative to the current welding methods for polyamide 6.
Friction spot welding (fspw) of polyamide 6
Keywords: Soldagem; Poliamida 6; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::METALURGIA DE TRANSFORMACAO